Estimation of Groundwater Quality in Arid Region or Semiarid Region by Using Statistical Methods and Geographical Information System Technique - Ahmed A. S. Alothman; Mohamed Saad Ahmed; S. Radjarejesri; G. Ramkumar; Ram Prasad; Panuganti Lakshmi; Mika Sillanpaa; Subash Thanappan (International Journal of Photoenergy)
This study takes place in year of 2021 during the premonsoon and postmonsoon seasons and twenty water samples were collected. Chemical factors like chloride, fluoride, sulphate, nitrate, and phosphate were measured in water samples. There is a significant difference in anion dominance between pre- and postmonsoonal (PRM and POM) water samples. The following anions are HCO3>TDS>Cl−>SO42−>TH>NO3>F−>PO4 and TDS>HCO3−>SO42−>Cl−>TH>NO3−>F−>PO4−. In both seasons, particular way of cations is Na+>Ca2+>Mg2+>K+. SAR, Kelly’s ratio, residual sodium carbonate, potential salinity, permeability index, and sodium percentage were used to evaluate the irrigation water quality. To investigate the geochemical regulation and hydrogeochemistry of groundwater, two approaches were used: according to the findings, groundwater in various parts of the investigation was determined to be unfit for human consumption.